Neuromuscular demand in a soccer match assessed by a continuous electromyographic recording - Montini, M.; Felici, F.; Nicolò, A.; Sacchetti, M.; Bazzucchi, I. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The bulk of research investigating soccer player's performance has been concentrated on the metabolic demand, while only few studies focused on the neuromuscular activation. The present study aimed at investigating the activation profile of the leg muscles throughout a 90- minute soccer match.